2021
DOI: 10.1038/s41598-021-88203-w
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear magnetoelectric effects in Al-substituted strontium hexaferrite

Abstract: This report is on the observation and theory of electric field E induced non-linear magnetoelectric (NLME) effects in single crystal platelets of ferrimagnetic M-type strontium aluminum hexagonal ferrite. Using microwave measurement techniques, it was found that a DC electric field along the hexagonal c-axis results in significant changes in the saturation magnetization and uniaxial magneto-crystalline anisotropy field and these changes are proportional to the square of the applied static electric field. The N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
4
1
Order By: Relevance
“…Hence, if Δ(4πM0) is linearly proportional to the applied power [21][22][23][24], then the shift Δfr also should be proportional to P which agrees with the results in Fig. 7.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Hence, if Δ(4πM0) is linearly proportional to the applied power [21][22][23][24], then the shift Δfr also should be proportional to P which agrees with the results in Fig. 7.…”
Section: Discussionsupporting
confidence: 86%
“…Studies on c-plane single crystals of (Sr,Al)-and Ba-hexaferrites also revealed a similar NLME effects for currents either in the c-plane or along the c-axis [23,24]. E-tunable resonators and filters of M-and Y-type hexagonal ferrites operating at 12-50 GHz were demonstrated [25][26][27].…”
Section: Introductionmentioning
confidence: 69%
“…In ferrite, Fe 3+ on the lattice transforms into Fe 2+ . [ 39 ] During this transformation, the jumping of electrons induces a conductive phenomenon. When the frequency of the jumping electrons aligns with the frequency of the applied electric field, the dielectric loss undergoes a sudden change.…”
Section: Resultsmentioning
confidence: 99%
“…6,26 For instance, preoperative and postoperative neoadjuvant chemotherapy with doxorubicin (DOX) and anthracycline, lacking a delivery mechanism, induces cardiac side effects and adverse reactions in patients with breast cancer. 27 These drawbacks have spurred the development of smart drug delivery systems like hydrogels, nano-vesicles, liposomes, and microneedles for controlled local release. 28,29 Lately, hydrogel delivery systems have gained attention due to their ability to minimize toxic drug effects while demonstrating excellent controlled release and biodegradability.…”
Section: Introductionmentioning
confidence: 99%